The Effect of Government Expenditures on Education, Health And Per Capita Revenue To The Human Development Index Of Regency / City In West Kalimantan Province - B1011131120, Syarifah Selvi Ersa Destari (Jurnal Pembangunan dan Pemerataan, 2017)
Development is one of the processes that is carried out by the government by applying policies to achieve public welfarw. The purpose of this research is to test the influence of the expenditure of theÂ  Government Sector of Education, Health, and Income Per Capita towards the Human Development Index on the regency/city in the West Kalimantan province. This research uses quantitative method and the data is analyzed using multiple linear regression model with common effect weight model. The data sources are obtained from Central Bureau of Statistics and Directorate General of Regional Financial Balance. The result of research shows that the expenditure of the government sector of education has positive influence and is not significant towards the Human Development Index for regency/city in West Kalimantan province, while the expenditure of the government sector of health and income per capita have positive influences and are significant towards the Human Development Index for regency/city in West Kalimantan province.Â Keywords: Human Development Index, the expenditure of the government sector of education, health, and income per capita.